THE ROLE OF MEDAN HELVETIA SECTOR POLICE IN ENFORCING NARCOTICS CRIME - Dedek Syafrizal; Lubis, Junaidi; Debi Masri; Leni Indrayani (JIL : Journal of Indonesian Law, 2025)
This research aims to analyze the role of Medan Helvetia Sector Police (Polsek) in enforcing narcotics crimes, as well as identifying strategies and obstacles faced in the implementation process. Using a juridical-empirical approach, this research combines primary data through observation and interviews with secondary data in form of legal documents and related literature. The results show that Medan Helvetia Police carry out a strategic role through three main approaches, namely promotive, preventive, and repressive. The promotive approach is realized in form of counseling and education to the community, while the preventive approach involves monitoring vulnerable areas and cross-sector cooperation. Repressive measures are carried out through routine operations, arrests, and strict law enforcement against perpetrators. The main obstacles faced include the lack of community reports, limited resources, and complexity of drug trafficking networks. Therefore, the effectiveness of law enforcement requires stronger synergy between police officers and community participation in creating a drug-free environment. The findings confirm the importance of a collaborative and sustainable approach to tackling drug crime at the local level.